Analysis of the Natural Convection Flow in the Upper Plenum of the MONJU Reactor with Trio_U. (30th May 2013) - Bieder, Ulrich; Fauchet, Gauthier
Abstract : The IAEA has coordinated a benchmark project on natural convection phenomena in the upper plenum of the MONJU reactor. JAEA has provided both detailed geometrical data of the plant and complete thermalhydraulic boundary conditions describing a pump trip transient, accomplished during the start-up experiments of the reactor. For the initial conditions of the pump trip transient, extensive sensitivity analyses have been made with the CFD code Trio_U. These calculations show a high sensitivity of the global flow pattern in the MONJU upper plenum depending on the initial order of the numerical scheme and the modelling of the geometrically complex upper core structure. During the pump trip, the formation of a thermal stratification within the plenum has been observed which persists for almost two hours. All calculations have shown a homogenization of the temperature in the plenum after about 15 minutes. A slight reduction of the mixing in the upper plenum could have been achieved by modifying the form of the flow holes in the inner barrel (fillets instead of sharp edges) in order to reduce their axial pressure loss.